Investigating Foreign Language Anxiety among Middle School Learners :The Case of Fourth Year Pupils in Djaber Ben Hayen Middle School School,M’sila - Mansour, Fayza (My University, 2018)
ii Abstract The present study aims to examine the level of foreign language anxiety experienced by fourth year pupils in Djaber Ben Hayen Middle School . Thus , to reach our objectives, we conducted two main questionnaires the first one aimed to investigate the level and the sources of FL anxiety among middle school learners ; whereas , the second was directed to language teachers to examine whether they are aware about this problem and whether they are working to find some effective solutions to reduce anxiety in their classes, The findings of our present study revealed that middle school pupils indeed had a moderate level of anxiety resulted from : communicative apprehension , fear of negative evaluation ,fear of failing in language tests. The students‟ lack of self- confidence let them fear of peers in particular .They also believe that teachers „ questions and error correction in the classroom are the main sources of anxiety . Finally , in an attempt to find some solutions , we propose some strategies that the classroom atmosphere should be motivating and encouraging . Teachers are recommended to deal with anxiety-provoking situations carefully as they are the most involved part in this process.
Keywords: Keywords: anxiety, fear, test, comprehension, performance, communication, failure, low self-esteem, unconfident, learner, teacher, facilitator, sweatnig, hesitation, test anxiety, negative evaluation.